A Comprehensive Communication Approach to Navigate the Crisis Caused by Online Gambling: Insights from Kemencast #44 on Youtube - Chamil, Andika Yulianto; Djuanda, Safiera Amanda; Septaviana, Nurina (Ilomata International Journal of Social Science, 2024)
The COVID-19 pandemic has presented serious challenges to people's mental health, with increasing cases of online gambling addiction being of particular concern. Kemencast YouTube content case study #44 illustrates the complexity of online gambling addiction during the pandemic. This research aims to explore this by focusing on the trigger factors, impacts, and comprehensive communication approaches in dealing with mental health crises related to online gambling addiction. The research method used is qualitative by collecting data through content analysis of a podcast entitled "Love Your Mentality, Don't Get Broken Because of Online Gambling." The research results identified the trigger factors, impacts and the important role of communication in overcoming these problems. The research results show that social isolation, economic uncertainty, increased use of technology, and stress are factors that trigger online gambling. The impacts include mental health problems, financial losses, and social relationship problems. A comprehensive communication approach, including education, prevention, support, and elimination of stigma, is needed to address this problem.